Effect Of Plant Growth Regulators On Growth And Productivity In Yard Long Bean - Resmi R (Department of Olericulture, College of Horticulture, 2001)
Studies on the "Effect of plant growth regulators on growth and productivity in yard long bean (Vigna unguiculata var. sesquipedalis (L.) Verdcourt)" was conducted at the Department of Olericulture, College of Horticulture, Kerala Agricultural University, Vellanikkara, Thrissur during rabi (September, 2000 to January, 2001) and summer (February, 2001 to May, 2001) seasons using the variety 'Lola'. Four plant growth regulators (NAA, 2,4-D, PCPA and CCC) at three concentrations each, constituted twelve treatments excluding water spray and non-treated control. The experiment was laid out in a Randornised Block Design (RBD) with three replications. NAA (15, 30 and 45 pp m) was sprayed thrice at 30, 45 and 60 days after sowing (DAS) and CCC (300, 400 and 500 pp m) at 20 DAS in both rabi and summer seasons. During rabi season 2,4-D (2, 4 and 6 pp m) and PCPA (25, 50 and 75 ppm) were applied at 30, 45 and 60 DAS and during summer at 45 and 60 DAS. NAA and CCC at lower concentrations (15 ppm and 300 ppm respectively) were effective for the growth and productivity in both the seasons. In case of vegetative characters, NAA at 15 ppm produced maximum vine length (6.58 m) and CCC at 300 ppm produced maximum number of secondary branches (18.67). CCC (300ppm) application resulted in early flowering (39.33 days) and harvest (46 days) during rabi. NAA and CCC at lower concentrations were equally effective for increasing the fruit set by reducing the flower and pod shedding in both rabi and summer seasons. Spraying of 2,4-D and PCPA at all concentrations resulted in vegetative malformations like curling, cupping and strap shaped leaves without any leaflets, long internodes, funnel shaped leaves with bushy and stunted appearance when